The Diversity of Creatures and The Oneness of God in His Creation - Muhammadong Muhammadong (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this research is to describe the diversity of creatures and the oneness of God. The plurality that occurs among the people will trigger various conflicts in various fields. Conflict has become a phenomenon in life because of various interests. However, plurality will trigger sectarianism within religions which can disrupt diversity. The oneness of God certainly cannot be influenced by the plurality of creatures. The oneness of God becomes transcendental so that creatures do not mix in the plurality of creatures. The method used in this research is descriptive qualitative by presenting religious phenomena in society. Data used through literature to find the truth in the plurality of creatures. The research results show that the diversity of creatures cannot affect the oneness of God. Diversity is a phenomenon that can bring harmonization of life so that it is more convincing of the oneness of the creator.